Equity and Efficacy in Washington State's GMA Affordable Housing Goal - Henry W. McGee Jr. (Washington University Journal of Law & Policy, 2000)
This Essay considers the basis for the Growth Management Act’s affordable housing goal, considers the relationship between its achievement and the reduction of urban sprawl. It also links the Growth Management Act’s goal of an equitable distribution of housing resources to a fundamental social aspiration described by the United States Congress as a “decent home and living environment for all Americans.” Indeed, it will be argued that the economic disparity and inequity directly linked to urban sprawl—both a cause as well as an effect—are locked ineluctably to a pathological social process in which they feed upon each other. Continued environmental degradation, which has spawned the salmon crisis, has exacerbated the housing crisis, making more challenging its resolution. However, legislative gridlock frustrates efforts at crafting a strategic and regionally coordinated response to the challenge of affordable housing.
Keywords: Land use; Regional planning; Washington. Growth Management Act of 1990